2001
DOI: 10.1128/mcb.21.4.1155-1163.2001
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of a Specific Promoter Nucleosome Accompanies Activation of the ɛ-Globin Gene by β-Globin Locus Control Region HS2

Abstract: On stably replicating episomes, transcriptional activation of the -globin promoter by the ␤-globin locus control region HS2 enhancer is correlated with an increase in nuclease sensitivity which is limited to the TATAproximal nucleosome (N1). To elucidate what underlies this increase in nuclease sensitivity and the link between chromatin modification and gene expression, we examined the nucleoprotein composition and histone acetylation status of transcriptionally active and inactive promoters. Micrococcal nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Reactions were performed in a final volume of 400 ml in dilution buffer (0.01% SDS, 16.7 mM Tris-HCI (pH 8.1), 1.2 mM EDTA, 150 mM NaCl and 1% Triton X-100) plus 3 mg of the appropriate primary antibody and rotated overnight at 41C. HDAC1 and p300 antibodies were purchased from Santa Cruz Biotechnologies, anti-acetylatedhistone H3 monoclonal antibodies were purchased from Upstate Inc. (Chicago, IL, USA) (Benjamin and Jost, 2001;Chaya et al, 2001;Gui and Dean, 2001;Dey et al, 2003) whereas secondary anti-mouse antibody was purchased from Pierce Biotechnology Inc. (Rockford, IL, USA). Four hundred microliters of Protein A Sepharose beads (30 mg/ml in dilution buffer) was then added to each reaction and rotated for 2 h at 41C.…”
Section: Chip Assaysmentioning
confidence: 99%
“…Reactions were performed in a final volume of 400 ml in dilution buffer (0.01% SDS, 16.7 mM Tris-HCI (pH 8.1), 1.2 mM EDTA, 150 mM NaCl and 1% Triton X-100) plus 3 mg of the appropriate primary antibody and rotated overnight at 41C. HDAC1 and p300 antibodies were purchased from Santa Cruz Biotechnologies, anti-acetylatedhistone H3 monoclonal antibodies were purchased from Upstate Inc. (Chicago, IL, USA) (Benjamin and Jost, 2001;Chaya et al, 2001;Gui and Dean, 2001;Dey et al, 2003) whereas secondary anti-mouse antibody was purchased from Pierce Biotechnology Inc. (Rockford, IL, USA). Four hundred microliters of Protein A Sepharose beads (30 mg/ml in dilution buffer) was then added to each reaction and rotated for 2 h at 41C.…”
Section: Chip Assaysmentioning
confidence: 99%
“…P19 cells treated with vehicle (control) or 10 Ϫ6 M RA for the indicated days were cross-linked with 1% formaldehyde for 15 min, followed by the addition of 1.47 ml of 1 M glycine/10 ml culture to stop cross-linking. The procedures were performed with some modifications as described previously (Gui and Dean, 2001). The nuclei isolated from ϳ10 8 cells (four plates) were suspended in 1 ml of wash buffer (10 mM Tris-HCl, pH 7.4, 15 mM NaCl, 50 mM KCl, 0.15 mM spermine, 0.5 mM spermidine, and 8.5% sucrose) and digested with micrococcal nuclease (MNase; 30 -120 U; Worthington Biochemical, Freehold, NJ) or DNase I (2-30 mg/ml) for 6 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…5 Recent studies have suggested that some DNaseI-hypersensitive sites, such as that of the human ε-globin promoter, may still be bound by a nucleosome but with an altered structure. 6 DNaseI-hypersensitivity is therefore a structural marker for the disruption of the regular nucleosomal array caused by the formation of specific nucleoprotein complexes by the co-operative binding of ubiquitous and tissue-specific transcription factors 7,8 to exclude or modify nucleosomes. The high-density of transcription factors makes it likely that such sequences will be cis-acting regulatory elements, such as promoters and enhancers.…”
Section: Introductionmentioning
confidence: 99%